Paradoks Pekerja Rumah Tangga di Indonesia: Belum Tergolong Pekerja Yang Melakukan Pekerjaan Layak? - Naben, Kristianto Ratu Marius (Yayasan Literasi Sains Indonesia, 2023)
This article is an analysis of the paradoxical situation experienced by domestic workers in Indonesia. On the one hand, they exist as workers, but on the other hand, their existence as workers has not been recognized and their rights as workers have not been fully fulfilled and they do not receive social protection guarantees from the government. This position makes them vulnerable to exploitation, violence and oppression. Therefore, by using qualitative research methods, especially literature studies based on literature and previous research results, the author shows the social exclusion of domestic workers in Indonesia. Based on the facts above, the author emphasizes the importance of applying the concept of decent work for domestic workers and promoting domestic work as a decent work for domestic workers. One conclusion that can be drawn from discussing this topic is that domestic workers also count as workers and that domestic work is also decent work that should be widely accepted. With this recognition, the existence of a legal umbrella and guaranteed social protection for domestic workers is a must. Thus, recognizing the existence of domestic workers and their work is an intention to build an inclusive social order, in which there is recognition and respect for a person's dignity.